TINJAUAN IJMA’ TERHADAP KONSEP BAI’AL-WAFA’ - Riskiyah, Rofiqotur (Universitas Muhammadiyah Surabaya, 2021)
This study aims to find out about how Ijma 'review of the concept of bai'al-wafa'. This study uses Library Resech research with a descriptive approach. The data sources of this research were collected from several books and journals which were analyzed using the Miles and Huberman analysis method which includes three lines, namely data reduction, data presentation and conclusion or verification. The results of this study concluded that from the results of the ijma'para ulama about bai'al-wafa 'there were differences of opinion, where the opinions of both were strengthened by the arguments and reasons of each ulama. According to the hanafiyah ulama, the occurrence of bai'al-wafa 'is allowed because the purpose of using bai'al-wafa' is to avoid usury which continues to grow among the community. Bai'al-wafa 'when viewed from ihtihsan' urf, which is something that has been carried out by society and has been considered good. Meanwhile, according to the jumhur of other scholars, the bai'al-wafa 'is not allowed, because in the sale and purchase there is no grace period and conditions that state that the purchased goods must be returned to the original owner at the same price, therefore according to the scholars the use of bai'al-wafa 'is not justified.Keywords : Bai’al-Wafa’, Consept Bai’al-Wafa’, Ijma’